Pengelolaan Kecerdasan Emosi Pendidik TK Azhari Islamic School Jakarta - Dwi Eka Adhariani; Akhmad Shunhaji; Abd. Muid Nawawi (Departement of Mathematics Education, 2023)
This research concludes that the management and measurement of emotional intelligence (EQ) of Azhari Islamic School Kindergarten educators experience many obstacles in carrying out online (online) learning through smartphone applications during lockdown, such as: teaching loss, stress-inducing boredom, limited skills in using gadgets and learning applications, internet network disturbances and funds, and lack of understanding of the character and characteristics of students. This is motivated by problematic emotional problems that arise as a result of the impact of the Covid-19 pandemic in Indonesia which affects all aspects of life including the education process in PAUD. This research shows that there is a process of managing and measuring emotional intelligence (EQ) of Azhari Islamic School Jakarta Kindergarten educators based on Daniel Goleman's emotional intelligence theory. The process of managing the EQ of educators at the Azhari Islamic School Jakarta Kindergarten through intensive training and self-development programs from foundations and independently. The results of measuring the emotional intelligence of educators at Azhari Islamic School Jakarta Kindergarten show that overall the five aspects of Goleman's emotional intelligence (self-awareness, self-regulation/emotional management, motivation, empathy and social skills) have high and good emotional intelligence with an average percentage of 80.4% . Aspects of the ability to manage emotions produce the highest score of 94.79%. And on the results of measuring the aspect of fostering external relations which has a percentage of 72.42% (enough category)